2020
DOI: 10.3390/coatings10040332
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Grain Ni/ZrO2 Functional Gradient Coating Fabricated by Double Pulses Electrodeposition with Enhanced High Temperature Corrosion Performance

Abstract: Functional gradient materials (FGM) have many excellent properties, and high-performance gradient coating exhibits good prospective application. In this paper, the nano-grain Ni/ZrO2 gradient coating was prepared by double pulse electrodeposition (BP). The surface morphology, crystal structure and electrochemical corrosion resistance of the nano-grain Ni/ZrO2 coating and Ni coating, annealed at different temperatures (400–800 °C), have been compared. In the vertical direction to the substrate surface, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Probably, the opposite behavior of the mechanical properties is associated with the difference in the processes activated by heat treatment, both in the material volume and on the surface. We concluded that three complex processes significantly affect the mechanical properties of the system after analyzing the investigation results and literature [24][25][26][27]30,35,39,48]:…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Probably, the opposite behavior of the mechanical properties is associated with the difference in the processes activated by heat treatment, both in the material volume and on the surface. We concluded that three complex processes significantly affect the mechanical properties of the system after analyzing the investigation results and literature [24][25][26][27]30,35,39,48]:…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the choice of pulse duration allows for you to select the desired grain size. More detailed control of the microstructure by varying the pulse duration is described in the previous article [ 38 , 39 , 40 ]. Complex electrolyte was used for NiFe electrodeposition.…”
Section: Methodsmentioning
confidence: 99%
“…The current density of DC electroplating is much lower than the peak current density of pulse electroplating. Pulse electrodeposition not only has an effect on the morphology of the plated layer, but also on the corrosion resistance of the plated coating [23][24][25][26][27][28]. However, the mechanism of the effects of pulse electroplating parameters on the morphology and corrosion resistance of silver coatings have received little attention.…”
Section: Introductionmentioning
confidence: 99%